Lectotypification of Merremia rhyncorhiza (Convolvulaceae) - Kolte, R. R.; Shimpale, V. B.; Janarthanam, M. K. (Rheedea, 2017)
Merremia rhyncorhiza (Dalzell) Hallier f. (≡ Ipomoea rhyncorhiza Dalzell) (Convolvulaceae) is lectotypified here.